MIĘDZYKULTUROWOŚĆ JAKO PRZESTRZEŃ DLA TRANSDYSCYPLINARNEJ METAANALIZY W GLOTTODYDAKTYCE I PEDAGOGICE MIĘDZYKULTUROWEJ – POLA WSPÓŁ-/ NIEZALEŻNOŚCI POJĘĆ, PARADYGMATÓW I CELÓW KSZTAŁCENIA - Karpińska-Musiał, Beata; Orchowska, Izabela (Neofilolog, 2019)
The paper presents a critical reflection on the issue of transdisciplinarity in defining interculturality as an object of scientific cognition on glottodidac-tics and intercultural pedagogy. Specifically, the authors propose a compar-ative meta-analysis of conceptualization of terms and paradigms, as well as teaching aims connected with interculturality in these two disciplines. They pose the question whether the transdisciplinary orientation is appropriate for scientific modeling and for defining teaching objectives on the border-line between interculturality in glottodidactics and intercultural pedagogy.